2014
DOI: 10.5151/medpro-cihhs-10213
|View full text |Cite
|
Sign up to set email alerts
|

O Mundo da Criança Sendo-Com Câncer em Tratamento Oncológico Revelado por Meio do Brinquedo Terapêutico Dramático

Abstract: No Brasil, o câncer tem se destacado como um problema de saúde pública e, como a segunda causa de morte em crianças e adolescentes entre um e 19 anos. o câncer infantil é uma doença crônica que demanda um tratamento longo, desgastante, invasivo e doloroso e implica alterações nos hábitos de vida da criança e da família. É importante que a criança com câncer tenha uma boa qualidade de vida, diminuindo possíveis sequelas por meio de ações específicas que visem o bem-estar e proporcionem relações sociais e afetiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 0 publications
0
8
0
3
Order By: Relevance
“…Some studies inform that cancer produces feelings of fear, anxiety, and insecurity for the future and depressive symptoms in children [ 21 , 22 ]. Through play interventions, it has been found that depressive symptoms can be reduced in children with cancer who are hospitalized for long periods [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies inform that cancer produces feelings of fear, anxiety, and insecurity for the future and depressive symptoms in children [ 21 , 22 ]. Through play interventions, it has been found that depressive symptoms can be reduced in children with cancer who are hospitalized for long periods [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Children, depending on their developmental phase, are capable of not only reporting it, but also classifying it -indicating that they know their own limits -and recognize it as part of the healing and improvement process (14) . However, pain is subtracted mainly because it is not correctly evaluated and because the child's evaluation is little considered (19) . The report of hospitalized children's pain is mainly associated to the performance of some procedures, including new and repetitive ones, and the use of needles as a cause of pain has been reiterated in several studies (10,14) .…”
Section: Feeling Of Painmentioning
confidence: 99%
“…There are individual differences both in the acquisition process and in speed and quality (31) . Consequently, this development is complex and depends on a series of factors, ranging from neuropsychological maturation, affectivity, cognitive development, to contexts in which the child is inserted (19) .…”
Section: Information Received About Hospital Admissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Este brincar tem por objetivo promover ou restabelecer o bem-estar psicológico da criança por meio de atividades lúdicas. Tem sido muito utilizada para o tratamento de crianças com distúrbios emocionais, neuróticos ou psicóticos (FONSECA, 2014;THERENSE, 2019).…”
Section: O Papel Do Brincar Na Psicanáliseunclassified